Investigation of Enrofloxacin and Chloramphenicol Residues in Broiler Chickens Carcasses Collected From Local Markets of Tabriz, Northwestern Iran - Vahideh Ebrahimzadeh Attari; Mehran Mesgari Abbasi; Nasim Abedimanesh; Alireza Ostadrahimi; Abolfazl Gorbani (Tabriz University of Medical Sciences, 2014)
Background: The present study was aimed to determine the residual amounts of chloramphenicol and enrofloxacin in broiler chickens muscle and liver samples gathered from local markets of Tabriz City, northwestern Iran. Methods: Ninety broiler chickens carcasses were collected from different local markets of Tabriz, during July/August 2013. Random samples of thigh and breast muscle and liver were gathered and kept at -80C until analyzes. The samples were then assayed using enzyme-linked immunosorbent assay (ELISA) according to the protocol of each antibiotic kit. Data were statistically analyzed using the computer program SAS 9.1. Results: Eighty two samples (91/1 %) contained residues of enrofloxacin, although mean (±SD)of enrofloxacin concentration was lower than the European Union maximum residue limits(MRLs) value (P<0.001). Moreover, 28 (31/1 %) had detectable concentrations of chloramphenicol while it was not defined any MRLs value for chloramphenicol because its using has been forbidden in food animals. Conclusion: The frequency of contamination with enrofloxacin was considerable for the analyzed samples. Furthermore, the existence of chloramphenicol in almost one third of samples seems to be a public health threat due to its illegal use in food animals including poultry.